1993
DOI: 10.1116/1.586708
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of gas-assisted focused ion beam etching

Abstract: Gas-assisted etching with a finely focused ion beam has been studied. The presence of a reactive gas, in this case Cl2, results in an enhanced etch rate compared to the rate for sputtering for many materials, including Si, Al, and GaAs. Other advantages over sputtering are the absence of redeposited material and the high etch selectivity possible with some material combinations, which has been exploited in the etching of microstructures. In some applications of this technique, a protective layer of low etch ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…This process greatly enhances the etch rate, as was also reported for other adsorbed halogens. 38 Figure 2 ͑data points marked as ᭺͒ shows the measured excess losses in waveguides etched with the same dose as previously ͑5 ϫ 10 15 Ga + / cm 2 ͒, but with iodine atoms adsorbed to the surface. From the measurements we have extracted an excess loss of 1690± 90 dB/ cm.…”
Section: B Iodine Enhanced Etchingmentioning
confidence: 99%
“…This process greatly enhances the etch rate, as was also reported for other adsorbed halogens. 38 Figure 2 ͑data points marked as ᭺͒ shows the measured excess losses in waveguides etched with the same dose as previously ͑5 ϫ 10 15 Ga + / cm 2 ͒, but with iodine atoms adsorbed to the surface. From the measurements we have extracted an excess loss of 1690± 90 dB/ cm.…”
Section: B Iodine Enhanced Etchingmentioning
confidence: 99%
“…Thus, the severity of redeposition is a function of both Y t and the trench proportions. The mechanism that has been proposed to explain the "Classic V Shape"~Yamaguchi et al, FEI Focused Ion Beam Application Note, 1993;Walker, 1993;Young et al, 1993b;Ishitani et al, 1994;Bender et al, 1998! can be instructive in illustrating how the observed limits on aspect ratios attainable by FIB milling are caused by redeposition.…”
Section: Sputtering Ratementioning
confidence: 99%
“…There have been a few reports on Si and GaAs etching in the presence of a precursor gas to achieve enhanced etching rates and the interest was also focussed on the reduction in damage depth (14)(15)(16). We explored a possible way of controlling these nanodots by processing GaAs in the presence of XeF 2 , usually used for the enhanced etching of insulators.…”
Section: Introductionmentioning
confidence: 98%